A Proliferation of Cells - Pastorini, Jenna (Ars Medica, 2020)
This creative non-fiction piece is a product of my participation in a Medical Memoir course to fulfill my humanities requirement at Sidney Kimmel Medical College. I started the course approximately a month into my first year of medical school. My plight against the thinly veiled perception of tragedy, cancer and loss of a parent specifically, as glamorous has bubbled beneath the surface of my consciousness for approximately 10 years. The course served as the perfect space to pour this out as I dissected how cancer was portrayed in this setting, medical school broadly and anatomy lab specifically, and how it insulted, complimented and validated my personal experience with the illness.